The COVID‐19 pandemic impact on independent and provider‐based rural health clinics’ operations and cancer prevention and screening provision in the United States - Zahnd, Whitney E.; Silverman, Allie F.; Self, Stella; Hung, Peiyin; Natafgi, Nabil; Adams, Swann Arp; Merrell, Melinda A.; Owens, Otis L.; Crouch, Elizabeth L.; Eberth, Jan M. (The Journal of Rural Health, 2023)
The COVID-19 pandemic has disrupted cancer care, but it is unknown how the pandemic has affected care in Medicare-certified rural health clinics (RHCs) where cancer prevention and screening services are critical for their communities. This study examined how the provision of these cancer services changed pre- and peri-pandemic overall and by RHC type (independent and provider-based). We administered a cross-sectional survey to a stratified random sample of RHCs to assess clinic characteristics, pandemic stressors, and the provision of cancer prevention and control services among RHCs pre- and peri-pandemic. We used McNemar's test and Wilcoxon signed rank tests to assess differences in the provision of cancer prevention and screening services pre- and peri-pandemic by RHC type. Of the 153 responding RHCs (response rate of 8%), 93 (60.8%) were provider-based and 60 (39.2%) were independent. Both RHC types were similar in their experience of pandemic stressors, though a higher proportion of independent RHCs reported financial concerns and challenges obtaining personal protective equipment. Both types of RHCs provided fewer cancer prevention and screening services peri-pandemic-5.8 to 4.2 for provider-based and 5.3 to 3.5 for independent (P<.05 for both). Across lung, cervical, breast, and colorectal cancer-related services, the proportion of both RHC groups providing services dropped peri-pandemic. The pandemic's impact on independent and provider-based RHCs and their patients was considerable. Going forward, greater resources should be targeted to RHCs-particularly independent RHCs-to ensure their ability to initiate and sustain evidence-based prevention and screening services.